INCIDÊNCIA DE SÍNDROME METABÓLICA EM OBESOS DE PESO NORMAL E CONSUMO DE ALIMENTOS SEGUNDO O GRAU DE PROCESSAMENTO E FORÇA DE PREENSÃO MANUAL - COELHO, Carla Cristine Nascimento da Silva Coelho (2022)
The thesis objectives are to estimate the incidence of Metabolic Syndrome (MetS) in eutrophic individuals, in normal weight obese people (NWO) and in people with overweight and high body fat (BF) and to estimate the association between food consumption, processing degree and handgrip strength (HGS). Methods: prospective cohort study using data from a birth cohort initiated in 1978/79, Ribeirão Preto, São Paulo. The individuals were evaluated at two moments, aged between 23 and 25 years and between 35 and 37 years old and they were divided into 3 groups: eutrophic (BMI ≥ 18.5kg/m2 and < 25kg/m2 + ∑ skinfolds ≤ p90); NWO (BMI ≥ 18.5kg/m2 and < 25kg/m2 + ∑ skinfolds > p90) and BMI↑BF↑ (BMI ≥ 25kg/m2 + ∑ skinfolds > p90). Individuals identified with MetS at 23/25 years old were excluded from the analysis. At 35/37 years old, all of them were reevaluated regarding the MetS incidence and its components by Poisson regression with robust variance fit. We assessed food consumption at 23-25 years old through a Food Frequency Questionnaire and we analyzed food as a percentage of contribuition in kilocalories (according to the NOVA Classification). The HGS was evaluated at 37-39 years and it was used in an absolute and relativized way by the body mass index (HGS/BMI). Linear and non-linear regression were used to estimate the associations between food intake and HGS. Results: the NWO showed MetS risk ratio (RRadjusted=1.84; IC95%=1.35 – 2.50; p<0.001) similar to overweight individuals (RRadjusted=1.71; IC95%=1.39 – 2.11; p<0.001). Hypertriglyceridemia had significantly higher risk ratio among NWOs and hypertension had presented higher risk ratio among overweight. The absolute HGS had an average of 47.3 kg in men and 27.6 kg in women. The consumption in Total caloric intake (TCI) was 2274.5kcal/d with 51.3% contribution from in natura or minimally processed foods and aggregated culinary preparations (UNACP) and 37.8% from ultra-processed foods (UPF). A non-linear association was observed between consumption of UNACP and UPF with HGS and HGS/BMI. Consumption of UNACP up to 50% of the TCV is associated with a higher HGS (+2.3 kg), while consumption above 50% showed a lower HGS (-2.0 kg). As for the UPF, consumptions of up to 40% of the TCV are associated with a higher HGS (+1.5kg) and consumptions above this value are associated with a lower HGS (-2.1kg). Conclusions: The NWO have a similar MetS risk ratio to overweight individuals and high BF, this highlights the need to evaluate the amount of BF even in individuals classified as normal weight by BMI. Furthermore, our results suggest that food consumption according to the degree of processing interferes in a non-linear way in the HGS in adults.